Single nucleotide polymorphisms might influence chemotherapy induced nausea in women with breast cancer. (February 2017) - Oliva, Delmy; Nilsson, Mats; Andersson, Bengt-Åke; Sharp, Lena; Lewin, Freddi; Laytragoon-Lewin, Nongnit
Abstract: Background: Women receiving FEC (5 fluorouracil, epirubicin and cyclophosphamide) chemotherapy (CT) for breast cancer (BC) often experience side effects such as nausea and vomiting. Individual variations of side effects occur in patients despite similar cancer therapy. The purpose of this study was to investigate a possible genetic background as a predictor for individual variations in nausea induced by CT. Methods: 114 women were included in the study. All women received adjuvant CT for BC. Self-reported nausea and vomiting was recorded in a structured diary over ten days following treatment. Blood samples were collected before the treatment and used for the detection of 48 single nucleotide polymorphisms (SNPs) in 43 genes. SNPs from each individual woman were analyzed for their relation to the patient-reported frequency and intensity of nausea and vomiting. Results: Eighty-four percent ( n  = 96) of the women reported acute or delayed nausea or combined nausea and vomiting during the ten days following CT. Three out of the forty-eight SNPs in the following genes: FAS/CD95, RB1/LPAR6 and CCL2 were found to be associated with a risk of nausea. Conclusion: SNPs in the FAS/CD95, RB1/LPAR6 and CCL2 genes were found to be associated with nausea among women treated with adjuvant FEC for BC. SNPs analysis is fast and cost effective and can be done prior to any cancer therapy. The association between individual SNPs and severe side effects from FEC may contribute to a more personalized care of patients with BC.